Measurement of relative development capital markets in the countries in the region - Milošević-Avdalović Snežana; Milenković Ivan (Ekonomski Pogledi, 2016)
Measuring performance of stock market presents both a theoretical and practical challenge. Efficient financial markets considered the main condition for economic growth and development in developing countries and for developed countries. The aim of the study is to show the level of development and common features of capital markets in the countries in the region. The paper applied the techniques of descriptive statistics and correlation analysis in order to reach key results. The study covers eleven stock indices, three stock exchange indices (SP500, DJI, NIKKEI225) are indicators of changes in global capital markets while the remaining eight are indicators of changes in capital markets in the region (Serbia - BelexLine, Montenegro - Monex, Bosnia and Herzegovina - Birs and Sasx, Croatia - Crobex, Macedonia - MVI-10, Romania-BET, Bulgaria - Sofix).Analysis of the results observed countries in the region confirms the fact that capital markets in the countries in the region, mainly small and under-developed.